Asthma control and quality of life in a real-life setting: a cross-sectional study of adult asthma patients in Japan (ACQUIRE-2). (2nd September 2019) - Adachi, Mitsuru; Hozawa, Soichiro; Nishikawa, Masanori; Yoshida, Atsushi; Jinnai, Tatsunori; Tamura, Gen
Abstract: Objective : The level of asthma control in adult asthma patients receiving treatment in clinical practice from allergy and/or respiratory specialists in Japan remains unclear. We conducted the ACQUIRE-2 study (NCT02640742) to evaluate level of asthma control, asthma symptoms, health-related quality of life (HR-QoL), and reliever medication use in this setting. Methods : This observational study was undertaken between December 2015 and June 2016 in 58 medical institutions across Japan. We enrolled outpatients aged ≥20 years diagnosed with asthma for ≥1 year who were being managed by specialists. Criteria to evaluate the level of asthma control were based on modified definitions of the Asthma Prevention and Management Guideline 2015, Japan (JGL 2015) and Global Initiative for Asthma (GINA) 2012. Asthma symptoms, HR-QoL, and reliever medication use were also evaluated. Results : Of 1250 enrolled patients, 1175 were analyzed, 62.9% of whom were women. Mean (± standard deviation) age and duration of asthma were 59.7 ± 14.5 years and 16.9 ± 14.0 years, respectively. Using JGL 2015-based criteria, 24.4%, 69.2%, and 6.5% of patients had well-controlled, insufficiently-controlled, and poorly-controlled asthma, respectively. Using GINA-based criteria, 35.1%, 49.8%, and 15.1% of patients had controlled, partly controlled, and uncontrolled asthma, respectively. Daytime and nighttime asthma symptoms were experienced by 51.5% and 44.9% of patients, respectively. The mean MiniAQLQ score was 5.8 ± 1.0 (7-point scale). Conclusions : Asthma was not well-controlled in the majority of patients in this study. To achieve better asthma control, improvements in symptom monitoring and management may be required. Trial registration: ClinicalTrials.gov identifier: NCT02640742.